2002
DOI: 10.1016/s0272-6963(02)00037-2
|View full text |Cite
|
Sign up to set email alerts
|

Demand chain management in manufacturing and services: web‐based integration, drivers and performance

Abstract: This paper investigated the relationship between Internet-enabled supply chain integration strategies and performance in manufacturing and services. It summarizes the literature on demand and supply integration and describes four web-based strategies. A stratified random sample was collected from UK manufacturers and services, and there was strong evidence that demand chain management (DCM) led to the highest performance in manufacturing, but few signs of DCM in services. Manufacturers and services relying on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
361
2
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(388 citation statements)
references
References 54 publications
13
361
2
12
Order By: Relevance
“…Specifically, manufacturing and service firms may have differences in firm performance (Frohlich et al 2002). Thus, we used a dummy variable for the industry, with values of 1 and 0 for the manufacturing and service industries respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, manufacturing and service firms may have differences in firm performance (Frohlich et al 2002). Thus, we used a dummy variable for the industry, with values of 1 and 0 for the manufacturing and service industries respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The eight component (cost-efficiency in the demand and supply processes) implies that the components mentioned above should be carried out in a cost-efficient manner (e.g., Frohlich and Westbrook, 2002;Hines et al, 2002;Jüttner et al, 2007). In accordance with the macro management perspective of component two, cost-optimization should be conducted from a holistic and coordinated approach to avoid the inherent risk of sub-optimization associated with micro management.…”
Section: Figurementioning
confidence: 99%
“…The final component of DSCM identified in the literature review was cost-efficiency in the demand and supply processes (e.g., Frohlich and Westbrook, 2002;Hines et al, 2002;Jüttner et al, 2007). The company sources from a low cost country, and has adopted several strategies to reduce costs.…”
Section: Tablementioning
confidence: 99%
“…Frohlich found, in the context of web-based integration in supply chains, that reduction of internal barriers is a required first step before removal of supplier and customer barriers to achieve supply chain integration [20]. In a study of the automotive supply industry, Vickery found that there is a positive, causal relationship between integrative information technologies and supply chain integration, which comprised both horizontal integration (within a firm) and vertical integration (with suppliers and customers) [21].…”
Section: Irim and Erimmentioning
confidence: 99%